Community-Led Ethnobotanical Triage: Case study—Myaamia corn traditions - Gonella, Michael P.; Baldwin, Daryl W.; Greenberg, Adolph M. (Ethnobotany Research and Applications, 2016)
Rapid loss of indigenous ethnobotanical traditions has created a need to triage research efforts to preserve this traditional knowledge. A triage process, however, is best led by those who understand the cultural context of historical data and are keenly aware of the community’s pressing needs—the indigenous community itself. Non-community researchers can be involved by lending research skills and connections towards the community-established research goals. This study described a process by which two non-indigenous community researchers supported an indigenous, Myaamia (Miami) research scholar in triaging Myaamia ethnobotanical research priorities and in conducting a focused study on the highest priority plant according to that community: corn (Zea mays L.). Data gathered regarding Myaamia corn traditions allowed the reconstruction of the traditional corn cultivation cycle. Description of traditional corn processing techniques, recipes, and identifying traditional corn varieties is helping the Myaamia community in their efforts to preserve cultural historical knowledge associated with planting of corn and in so doing revitalize Myaamia language and culture.